(untitled) (Journal of Economic Research & Business Administration, 2021)
The article considers main aspects of transparency and accountability of government initiatives on the example of the project of a new remuneration system for civil servants. Therefore, the author analyzes the project’s cost effectiveness in the context of a three-year period and two pilot bodies in order to develop recommendations for improving transformation processes. A special formula was developed and calculations were made taking into account the method of cost-effectiveness analysis based on the factors of the conceptual model of the author’s dissertation research. Thus, in addition to the effects indicated in the media by the authorized body (the project developer) on the factor “Human capital”, the study also covers a wider range of aspects, namely, factors such as “Leadership”, “Strategy”, “Organization”, “Resources” through the prism of “Citizen Centricity”. It was found that there were no significant positive changes in performance during the analyzed period. And in some areas of work (such as “Organization”, “Citizen Centricity”), there is a deterioration in results. Thus, the author summarizes the activities of local executive bodies as ineffective in relation to a two-fold increase in the wage fund. Taking this into account and the identified “bottlenecks”, a number of recommendations for improving the activities, including legislative initiatives, are proposed. In general, the results of the study have direct practical significance, since they build a platform for scaling the analysis to the remaining pilot bodies in order to make timely changes during the piloting of the new remuneration system.